Design and Validation of a Contextualized Worksheet Using an Otok-Otok Boat to Support Applied Thermodynamics Learning - Habibah Khusna Baihaqi; Sudarti, Sudarti; Arimurti, Dyah Arum (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2025)
Conventional thermodynamics instruction frequently fails to bridge the gap between mathematical derivations and observable energy transfers, leaving students struggling to visualize cyclic processes in real systems. This study aims to develop and evaluate a contextualized worksheet using the otok-otok boat—a traditional steam-powered toy—as a real-world case study to support students' conceptual understanding. The research followed the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The worksheet was validated by experts using the Aiken’s V index, yielding a range of 0.83 to 1, which indicates high content validity. The implementation involved 82 undergraduate physics education students, with evaluation data collected from 63 respondents through a mixed-method questionnaire. The results indicate that the developed worksheet successfully facilitates the exploration of key thermodynamic principles, including work and heat transfer, P-dV work, and the laws of thermodynamics, as evidenced by students' ability to articulate these concepts in their written tasks. While the otok-otok boat helped contextualize abstract concepts through observable processes, the results primarily reflect pedagogical usability and student engagement. Students perceived the learning experience as enjoyable and meaningful, supporting the worksheet's acceptability as an instructional tool rooted in local wisdom.